IMPACTOS ECONÔMICOS DO DESASTRE DA SAMARCO - Fabiano Martins Carvalho dos Santos; Hugo Almeida Carlos Satiro; Paulo César Encarnação; Maria Geralda de Miranda (TRF2, 2018)
This study aims to verify the way in which the environmental catastrophe provoked by Samarco impacted the economic activities of the most affected regions, such as Mariana, in Minas Gerais. Data for the study were sought in public and private institutions, such as the Ministry of Development, Industry and Foreign Trade, MDIC, National Department of Mineral Production, DNPM, Brazilian Institute of Geography and Statistics, IBGE, São Paulo Stock Exchange, BOVESPA, Companhia Vale do Rio Doce (CVRD) and the Brazilian Mining Institute, IBRAM. Firstly, a brief history of mining was presented at the local and national levels and an analysis was made of the economic participation of the mining activity at the national and local levels. Finally, after the presentation of data, a discussion was made, based on Ignacy Sachs (2002), which shows that the myopia of profit, which emphasizes short-term gains, was responsible for the disaster and that such practice needs to be strongly opposed, since it ends up neglecting socio-environmental aspects as important as financial ones, deconstructing all the economic relevance of the activity achieved over the years.